(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the authors makes the first attempt of scientific analysis of the activity of Evangelical Christians-Baptists, who were in opposition to official Council of ECB and institutions of local government, on the materials of Rivne region. The article shows the peculiarities of religious resistance among the believers of that region to the soviet legislation to the religious cults at that time and to the instructions of All-Union Council of ECB.